Community Preparedness Policy Model in the Adaptation For Danger and Risk of Kaba Volcano Eruption Selupurejang Sub-District - Saputra, Beben; Ahmad, Supriyono (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
As a disaster prone area, community preparedness is needed in the adaptation for danger and risk of volcanic disasters. This study aims to formulate community preparedness policy model in the adaptation for danger and risk of Kaba volcano eruption. This research is classified as a combination research (mixed methods). The data is processed and analyzed by AHP (Analytical Hierarchy Process). The results of this research showed that the community preparedness policy model in the adaptation for danger and risk of Kaba volcano eruption is as follows: aspects of compiling the zone of danger and risk (39.1), mapping the zone of danger and risk (23.0), does not build in the danger zone (13.3), does not carry out agricultural activities in the danger zone (10.2).